Assessment of the Elderly Patients’ Well-being and Daily Activity in Institution X - Bartašiūnienė, Vida; Petravičienė, Zita (Slauga. Mokslas ir praktika, 2024)
According to the forecasts by the EU Statistical Office (Eurostat), Lithuanian population is expected to continue ageing rapidly. By the beginning of 2060, it is expected that almost 37% of the Lithuanian population will be aged 60 and over, compared to 35% in the EU (the average of 27 countries). The changing socio-economic situation, constant stress at work and in personal life, increasing retirement age and growing global tension are affecting people’s well-being. Physical activity (in combination with other healthy lifestyle factors) can provide the elderly people with a real opportunity to prolong their years of active and independent life and decrease functional limitation as well as social isolation. Given that physical activity is undoubtedly recognised as an important indicator of the quality of life for the elderly, it shall be noted that its practical implementation remains the weakest aspect in Lithuania. The aim of the research was to evaluate the well-being and daily activities of the elderly patients in Institution X. To achieve the aforementioned goal, it was decided to conduct an anonymous quantitative questionnaire survey. The questionnaire was designed by the authors. The research was carried out from June to October 2023 with the participation of 90 respondents; the respondents were being cared for in Institution X. As many as 88 questionnaires were found appropriate for the research analysis. The research revealed that the majority of the respondents were completely dissatisfied with their current state (condition), never felt in a good mood, very often felt that they were living an empty life, and very often felt helpless. Only a minority of the respondents, who participated in the research, very often felt happy. The assessment of respondents’ opinions on their daily routines showed that more than a half of the respondents were completely dissatisfied with their daily activities. Additionally, half of the respondents reported that daily activities often were very tiring and difficult, very often caused a lot of tension. Furthermore, there was no respondent for whom daily activities did not cause any stress.
Keywords: state (condition); happy; helpless